Utilização da piraclostrobina sobre a produção de cereais de inverno - Venâncio, Bruno José (2019)
The objective of the experiment was to evaluate the productivity, physical and chemical composition, incidence of diseases and digestibility of wheat, white oats and black oats, in the vegetative stage, full vegetative stage, farinaceous grain stage and silage, submitted or not to the treatment with pyrazostrobin, in successive sections. A vegetative stage cut was performed, a second cut in full vegetative stage, preceded by the application of pyraclostrobin 10 days before each cut, and a cut in a stage of farinaceous grain where the material was ensiled. The parameters evaluated were dry matter yield, morphological composition, bromatology, incidence of diseases, percentage of chlorophyll a and b and digestibility of all cuts and resulting silage. The pyraclostrobin at vegetative and vegetative stages improved the leaf stem ratio, increased the crude protein content, modified the fibrous composition of the plant, decreased chlorophyll concentrations and altered in situ digestibility of forages and controlled the diseases evaluated in relation to to the control treatment. At the farinaceous grain stage, pyraclostrobin reduced the proportion of neutral detergent fiber and modified its composition, improving in situ digestibility and dry matter recovery of the resulting silage, as well as. Among the forages in the vegetative stage, white oats proved to be more propitious to cultivation, with higher productivity and lower fiber concentrations, already in the stage of farinaceous grain and silage the wheat was better due to productivity, together with the bromatological composition.